Usefulness of Ultrasound Examination in the Assessment of the Nail Apparatus in Psoriasis - Krajewska-Włodarczyk, Magdalena; Owczarczyk-Saczonek, Agnieszka (International journal of environmental research and public health, 2022)
The assessment of psoriatic nail changes in everyday practice is based exclusively on clinical symptoms that do not reflect the entire disease process in the nail apparatus. The use of imaging methods, especially widely available and inexpensive ultrasonography, creates the possibility of additional revealing and assessing grayscale of morphological changes of the ventral nail plate, nail bed, and matrix, as well as the attachment of the finger extensor tendon to the distal phalanx. What is more, it enables the assessment of inflammation severity in the power Doppler technique. A qualitative classification of nail plate morphological changes corresponding to the severity of psoriatic nail changes has been developed so far and attempts are being made to develop a quantitative method to assess not only the presence of changes but also the severity of inflammation. Nail ultrasonography is not commonly performed, although published studies indicate the possible use of this technique in the assessment of psoriatic changes in nail structures. It can be particularly useful in subclinical changes imaging, preceding clinical manifestation of psoriatic nail changes, enthesopathy: subclinical and in the course of psoriatic arthritis, as well as in the assessment of treatment efficacy. This review article aims to summaries the research on ultrasonography of the nail apparatus which has been carried out so far, taking into account its applicability in clinical practice.